Power allocation algorithm of full duplex cognitive relay network based on energy harvesting - Shibing ZHANG; Liuke HAN; Meijuan ZHANG (Tongxin xuebao)
To alleviate the shortage of spectrum resources and improve the power utilization of cognitive radio networks,a resource allocation algorithm of full duplex cognitive relay networks with energy harvesting was proposed.In the algorithm,the coefficient for power splitting of the relay and the transmit power of the secondary users were jointly optimized to maximize the throughput of the secondary users under the interference to primary users and energy harvesting constraints.Since the optimization of the algorithm was non-convex,it was transformed into two sub-optimizations,the sub-optimization of the coefficient for power splitting and the sub-optimization of the power transmitted of secondary users,which were the solvable convex sub-optimizations.Then,the final solution of the original optimization was obtained with the iterative algorithm.Simulation results show that the throughput of the proposed algorithm,can obtain 2 times throughput of the networks with half-duplex power splitting algorithm and 1.5 times throughput of the networks with full-duplex time switching algorithm.